Quality of bell pepper (Capsicum annuum L.) affected by drought condition : a thesis presented in the partial fulfilment of the requirements for the degree of Master of Philosophy at Massey University, Palmerston North, New Zealand - Zikki, Kemas Akhmad Farid (Massey University, 2020)
The climate change is predicted with an increasing number of droughts caused by rising global temperature and limited rainfall, thus generate water scarcity. This condition will be a great challenge for agricultural activities, to produce more resilient fruits and to select adaptable varieties as mitigation to global warming. Drought condition affects plant growth and production, especially in some crops that very sensitive to water scarcity such as bell pepper. This study aims to investigate the effects of various water stress conditions to bell pepper production and qualities, through limited water supply at half field capacity or constant mild water stress or half field capacity and intermittent severe water stress, compared to control (daily watering in full field capacity). By those different irrigation methods, we assessed plant morphology during vegetative and generative phase, as well as yield and fruit qualities of two bell pepper varieties, Cupra and Viper. We found that those both varieties in this study were physiologically able to adapt with water stress conditions, but Viper variety had more responsive physiological responses to water stress, showed by reduction on stomatal conductance and photosynthesis rate. Intermittent severe water stress may still appropriate to support the effective use of water (EUW) on both species, and Viper variety expressed better water use efficiency (WUE) by maximizing plant yield under stress. Since genetic-specific adaptation was found in this study, we suggested that the Viper variety had a better drought tolerant mechanism and produced more marketable yield that will benefit small farmers than the Cupra variety.
Keywords: 300802 Horticultural crop growth and development